2013
DOI: 10.1038/ismej.2013.133
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and metagenomic attributes of the rhodoliths forming the largest CaCO3 bed in the South Atlantic Ocean

Abstract: Rhodoliths are free-living coralline algae (Rhodophyta, Corallinales) that are ecologically important for the functioning of marine environments. They form extensive beds distributed worldwide, providing a habitat and nursery for benthic organisms and space for fisheries, and are an important source of calcium carbonate. The Abrolhos Bank, off eastern Brazil, harbors the world's largest continuous rhodolith bed (of B21 000 km 2 ) and has one of the largest marine CaCO 3 deposits (producing 25 megatons of CaCO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…Finally, the high species richness associated with long‐lived rhodoliths and the build‐up of their dead remains is attributed to their three‐dimensional structure (Foster et al ., ). Rhodolith beds provide a supporting service as ecosystem engineers, thus fostering complex ecological interactions (Barberá et al ., ; Nelson, ; Cavalcanti et al ., ).…”
Section: Ecosystem Values and Human Pressuresmentioning
confidence: 97%
“…Finally, the high species richness associated with long‐lived rhodoliths and the build‐up of their dead remains is attributed to their three‐dimensional structure (Foster et al ., ). Rhodolith beds provide a supporting service as ecosystem engineers, thus fostering complex ecological interactions (Barberá et al ., ; Nelson, ; Cavalcanti et al ., ).…”
Section: Ecosystem Values and Human Pressuresmentioning
confidence: 97%
“…As an essential component of photosynthetic communities, rhodoliths produce oxygen, consolidate substrata, and function as autogenic ecosystem engineers19. The deposition of CaCO 3 by marine algae is an essential process in the global carbon cycle20 and rhodoliths are recognized as foremost carbonate builders21. Furthermore, corallines are one of the major producers of dimethylsulfoniopropionate (DMSP)22, which, upon being metabolized by algal-associated bacteria, produces volatile compounds such as dimethyl sulfide (DMS).…”
mentioning
confidence: 99%
“…Complementing those data, a more recent work, employing pyrosequencing revealed a broader distribution of Archaea in corals [28], describing the presence of Euryarchaeota (45.61%), Thaumarchaeota (42.11%), and Crenarchaeota (10.96%). A metagenomic study of rhodoliths that form the largest CaCO 3 bed in the South Atlantic Ocean revealed that Thaumarchaeota was the dominant archaeal phylum in this kind of environment [35], again reinforcing previous findings of its higher abundance in deeper marine waters.…”
Section: Archaea In Aquatic Environmentsmentioning
confidence: 55%